Biofunctionalized microbead arrays for early diagnosis of breast cancer. (24th October 2018) - Vafajoo, Atieh; Salarian, Reza; Rabiee, Navid
Abstract: A high-performance method is suspension microbead arrays which facilitate HER2 recognition for rapid prognosis in its preliminary stages before cancer reaches to its metastases level or first prevalence of tumor growth. To achieve this goal, we synthesized gelatin microbeads by oil in water (o/w) emulsion method and the size and stability of micro-particles were optimized with different concentrations of glutaraldehyde. The non-toxicity of microbeads was proved by MTT assay. Then the Herceptin was immobilized on the microbeads surface by carbodiimide coupling method. FITC was used as a fluorescent marker for recognizing HER2 receptors on SKBr3 cancer cells (clinical sample) and the recognition was tracked by flow cytometry. Results showed significant discrimination between SKBr3 cancer cells sample concerning HER2 negative cancer cells as a control sample.